The new disease caused by a coronavirus (Covid-19) - Celso Ramos (Instituto Nacional de Salud Pública, 2020)
In this special communication of Salud Pública de México, a brief description of the main events of the new pathology (WHO has named as Covid-19) caused by coronavirus is discussed. The cases of Covid-19 occurred in China and the rest of the world are mentioned. At the same time is emphasized the effort that China and other countries around the world are making to contain the epidemic. Also, highlights the role that WHO and other international organizations are playing to prevent and control the epidemic.